2018
DOI: 10.1097/wnr.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metaproteomics analysis shows altered fecal microbiota signatures in patients with major depressive disorder

Abstract: Major depressive disorder (MDD) is a highly prevalent and debilitating mental illness, which is associated with disorder of gut microbiota. However, few studies focusing on detection of the signatures of bacteria in feces of MDD patients using proteomics approach have been carried out. Here, a comparative metaproteomics analysis on the basis of an isobaric tag for relative and absolute quantification coupled with tandem mass spectrometry was carried out to explore the signature of gut microbiota in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 26 publications
13
133
2
Order By: Relevance
“…Other authors have reported a decrease of this genus after antidepressant intervention, suggesting that Colinsella might represent a useful index for MDD management and treatment . Another study in a small cohort from the same group reported partly contrasting findings, given that Firmicutes, Actinobacteria, and Lachnospiraceae were increased in MDD patients, while Bacteroidetes and Proteobacteria were reduced . The authors concluded that such differences might have stemmed form different sample size, demographics, and statistical approach …”
Section: Mdd Is Associated With Altered Gut Microbiota Compositionmentioning
confidence: 99%
“…Other authors have reported a decrease of this genus after antidepressant intervention, suggesting that Colinsella might represent a useful index for MDD management and treatment . Another study in a small cohort from the same group reported partly contrasting findings, given that Firmicutes, Actinobacteria, and Lachnospiraceae were increased in MDD patients, while Bacteroidetes and Proteobacteria were reduced . The authors concluded that such differences might have stemmed form different sample size, demographics, and statistical approach …”
Section: Mdd Is Associated With Altered Gut Microbiota Compositionmentioning
confidence: 99%
“…We have published a meta-analysis suggesting that patients with irritable bowel syndrome were at higher risk of major depression [37], confirming the potential causal or bilateral relationship between microbiota disturbances and major depression. Several studies have shown microbiota disturbances in patients with major depression; these disturbances are summarized in Table 1 [38][39][40][41][42][43][44][45][46][47][48][49][50]. Probiotics yielded small but significant effects for depression (d = −0.24, p < 0.01) and anxiety (d = −0.10, p = 0.03).…”
Section: Microbiota-orientated Therapies and Their Interest For Majormentioning
confidence: 99%
“…Correspondingly, in vitro studies have shown that serotonin affects the growth of microbes such as Escherichia coli and Rhodospirillum rubrum, 8 and activates bacterial quorum sensing. 9 Several studies have found alterations in the gut microbiota composition of patients with major depression [10][11][12][13][14][15][16] and rodents with depressive-like symptoms. [17][18][19][20][21] Moreover, recent human population-based studies, 16,22,23 as well as rodent experiments, [24][25][26][27][28][29] showed that SSRIs modulate the gut microbiota composition, an effect that may be related to their in vitro antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%